Parents' incomes and children's outcomes: a quasi-experiment - Randall K. Q. Akee; William Copeland; Gordon Keeler; Adrian Angold; E. Jane Costello (Institute for the Study of Labor (IZA), 2008)
Identifying the effect of parental incomes on child outcomes is difficult due to the correlation of unobserved ability, education levels and income. Previous research has relied on the use of instrumental variables to identify the effect of a change in household income on the young adult outcomes of the households children. In this research, we examine the role that an exogenous increase in household incomes due to a government transfer unrelated to household characteristics plays in the long run outcomes for children in affected households. We find that children who are in households affected by the cash transfer program have higher levels of education in their young adulthood and a lower incidence of criminality for minor offenses. These effects differ by initial household poverty status as is expected. Second, we explore two possible mechanisms through which this exogenous increase in household income affects the long run outcomes of children - parental time (quantity) and parental quality. Parental quality and child interactions show a marked improvement while changes in parental time with child does not appear to matter.
urn:nbn:de:101:1-20080605150
Keywords: J24; 330; Cash transfer programs; quasi-experiment; educational attainment; criminality; difference-in-differences; panel data; Haushaltseinkommen; Sozialtransfer; Wirkungsanalyse; Kinder; Bildungsniveau; Eltern; Zeitallokation; North Carolina; USA